2000
DOI: 10.1093/toxsci/56.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Oil Fly Ash-Induced Elevation of Plasma Fibrinogen Levels in Rats

Abstract: Particulate matter air pollution (PM) has been associated with morbidity and mortality from ischemic heart disease and stroke in humans. It has been hypothesized that alveolar inflammation, resulting from exposure to PM, may induce a state of blood hypercoagulability, triggering cardiovascular events in susceptible individuals. Previous studies in our laboratory have demonstrated acute lung injury with alveolar inflammation in rats following exposure to residual oil fly ash (ROFA), an emission source particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 43 publications
3
32
0
6
Order By: Relevance
“…However, they are consistent with the results of a controlled human exposure Environmental Health Perspectives • VOLUME 109 | SUPPLEMENT 3 | June 2001 study that reported increases in plasma fibrinogen (35), as well as with the animal study (22). While further results will be necessary to sort out the conflicting reports in epidemiologic studies, the weight of the evidence suggests that airborne particles are associated with increases in fibrinogen.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, they are consistent with the results of a controlled human exposure Environmental Health Perspectives • VOLUME 109 | SUPPLEMENT 3 | June 2001 study that reported increases in plasma fibrinogen (35), as well as with the animal study (22). While further results will be necessary to sort out the conflicting reports in epidemiologic studies, the weight of the evidence suggests that airborne particles are associated with increases in fibrinogen.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Peters and co-workers reported an air pollution episode and daily variations in air pollution were associated with increased plasma viscosity (21). Gardner and colleagues reported increases in fibrinogen in animals exposed to urban particles (22). Human volunteers exposed to concentrated air particles also have increased levels of plasma fibrinogen (23).…”
mentioning
confidence: 99%
“…A related extrapulmonary impact of ROFA is an elevation in plasma concentrations of fibrinogen in exposed rats (42). …”
Section: Physiologic Biochemical Cellular and Molecular Effects Ofmentioning
confidence: 99%
“…12 After PM inhalation, the lung releases locally and into the systemic circulation pro-oxidative (ie, reactive oxygen species) or proinflammatory (ie, cytokines such as IL-6 and TNF-␣) mediators or both and vasoactive hormones such as endothelins. [13][14][15][16][17][18][19][20] Acute-phase reactions take place and lead to the increase in plasma of such reactants as C-reactive protein and fibrinogen. In the lung the secretion of adhesion molecules by inflamed endothelial cells results in binding and activation of leukocytes and platelets, formation of platelet-leukocyte conjugates, and generation of hemostatically active, tissue factor-bearing microparticles.…”
mentioning
confidence: 99%